COMPARATIVE STUDY OF APICALLY EXTRUDED DEBRIS AND IRRIGANT AFTER USING TWO ROTARY SYSTEMS (K3, RaCe) - Elka N. Radeva; Radosveta I. Vassileva (Peytchinski Publishing, 2014)
The aim of this in vitro study was to establish and compare the amount of debris and irrigant extruded apically after root canal preparation with two rotary systems (K3 and RaCe). Methods: Two groups of 24 extracted teeth with single canals were used. In group 1 (12 teeth) the root canals were instrumented using nickel-titanium K3 rotary instruments and "crown-down" technique. In group 2 (12 teeth) the root canals were instrumented using nickel-titanium RaCe rotary instruments and "crown-down" technique. Debris and irrigant extruded from the apical foramen were collected into pre-weighed vials (using Myers and Montgomery technique) and the amounts were determined. Time taken for each instrumentation technique was also determined. The data was input and processed using the statistical software package SPSS 17.0.1. Results: The amount of the debris extruded through apical foramen in group 1 (K3 files) was 0,225 mg and in group 2 (RaCe files) was 0,213 mg. The volume of the extruded irrigant was 0,247 ml in group 1 and 0,238 ml in group 2. Time taken for instrumentation was 8.3 min by RaCe files and 8.7 min by K3 files. The difference in the amount of debris and irrigant produced among two groups was not significant. Conclusions: It was concluded that the RaCe system induces less extruded debris and irrigant through the apical foramen, than the K3 system. The difference between two groups was not significant.